Lentibacillus kapialis sp. nov., from fermented shrimp paste in Thailand - Amnat Pakdeeto; Somboon Tanasupawat; Chitti Thawai; Somporn Moonmangmee; Takuji Kudo; Takashi Itoh (My University, 2007)
Two strains of strictly aerobic, moderately halophilic Gram-positive rods were isolated from fermented shrimp paste ('ka-pi') produced in Thailand. They produced a red pigment and grew optimally in the presence of 5-30 % NaCl. The diagnostic diamino acid in the cell-wall peptidoglycan was meso-diaminopimelic acid. The predominant menaquinone was MK-7. The major cellular fatty acid was anteiso-C(15 : 0). Phosphatidylglycerol, diphosphatidylglycerol and two unidentified glycolipids were found to be the major polar lipid components. The DNA G+C content was 41.2-41.6 mol%. Comparative 16S rRNA gene sequence analyses showed that strain PN7-6T was most closely related to Lentibacillus salarius KCTC 3911T with 96.5 % sequence similarity. On the basis of phenotypic and molecular properties, the two isolates represent a novel species of the genus Lentibacillus, for which the name Lentibacillus kapialis sp. nov. is proposed. The type strain is PN7-6T (=JCM 12580T=PCU 259T=TISTR 1551T).
Keywords: Genomics and Phylogenetic Studies